Disaster Mitigation Efforts Based on Hutan Larangan (The Forbidden Forest) Folktales of Dieng Plateau - Setiyoningsih, Titi; Secio Chaesar, Ari Suryawati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
One of the places in Indonesia that still treasures folklore and has become an international tourist destination is the Dieng Plateau. Tourist activities and deforestation for agricultural land pose environmental problems in the Dieng Plateau. Responding to these problems, it is necessary to conduct disaster mitigation efforts through the preservation of folklore. Based on the results of interviews in the Dieng Plateau, there are various folklores, including the Hutan Larangan (The Forbidden Forest). This study probed the types and functions of the Hutan Larangan folklore as a disaster mitigation effort in the Dieng Plateau. This research is descriptive qualitative. The primary data used in this study research consist of the Hutan Larangan folklore. The main data sources of this research are traditional community leaders and general residents of the Dieng Plateau. The data collection techniques conducted are interview and documentation techniques. The sampling technique of this research was carried out through the snowball sampling technique. The validity techniques used are source triangulation and theory triangulation. The data were analyzed through interactive analysis techniques. The results show that Hutan Larangan is a local legend that serves as an educational tool and a coercive tool as well as a supervisor so that the values or norms of the Dieng Plateau community will always be obeyed by the collective members or the community. Disaster mitigation through the Larangan folktale can be carried out through forest preservation using folktale of Hutan Larangan, digitalization of folktale of Hutan Larangan, and the selection of Indonesian Language in form of folktale of Hutan Larangan, especially for Junior High Schools in the Dieng Plateau